PENGARUH VARIASI KADAR EKSTRAK ETANOLIK DAUN KEMBANG SEPATU (Hibiscus rosa-sinensis L.) DALAM SIRUP TERHADAP AKTIVITAS MUKOLITIK SECARA in vitro - , LILIES WAHYU ARIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leaf hibiscus ( Hibiscus rosa - sinensis L. ) is a medicinal plant that can treat a variety of diseases , empirically hibiscus leaves are used as a cough medicine. To improve the aesthetics and the acceptability, the extract should be formulated in syrup dosage form. The aim of this research is to determine mucolytic activity of ethanol extracts of hibiscus leaves on bovine intestinal mucus in vitro in syrup dosage form based on physical properties and identify the components of the active compound from hibiscus leaves with densitometry . Ethanolic extracts of hibiscus leaves was made by maceration method using ethanol 70 %. The obtained ethanol extract was made series concentration started from 0,55 %